Unfolding the layers of LGBTQ+ identity, resilience, and multicultural perspectives in Vietnam - Lam-Nguyen, Huy (Frontiers in Sociology, 2025)
My personal narrative, intertwined with the theoretical acumen of Queer Theory and intersectionality framework, is used within this article as one way of underlining the critical role of lived experiences in forming an insight into LGBTQ+ identity and informing the strategies necessary to support this community. Drawing on Queer Theory, particularly the work of scholars like Jagose, which highlights the fluidity and complexity of identity, this research will analyze the intersectional challenges faced by individuals in specific non-Western regions, particularly in Southeast Asia. These experiences are examined through the employment of a reflexive thematic analysis approach, identifying recurring themes such as (1) gender nonconformity in childhood, (2) the pain of bullying and social pressures, (3) cultural transition and self-acceptance, (4) family support and unspoken understanding, and (5) interaction with LGBTQ+ Communities in Africa and the MENA Region.